Significant pain decrease in children with non-systemic Juvenile Idiopathic Arthritis treated to target: results over 24 months of follow up - Katinka Spekking; Janneke Anink; Piroska de Boer; Sytske Anne Bergstra; J. Merlijn van den Berg; Dieneke Schonenberg-Meinema; Lisette W. A. van Suijlekom-Smit; Marion A. J. van Rossum; Yvonne Koopman-Keemink; Rebecca ten Cate; Cornelia F. Allaart; Daniëlle M. C. Brinkman; et al. (BMC, 2023)
Abstract Background The aim of this study was to compare pain-scores in three targeted treatment-strategies in JIA-patients and to identify characteristics predicting persistent pain. Methods In the BeSt-for-Kids-study 92 DMARD-naïve JIA-patients were randomized in 3 treatment-strategies: 1) initial sequential DMARD-monotherapy 2) initial methotrexate (MTX)/prednisolone-bridging or 3) initial MTX/etanercept. Potential differences in VAS pain scores (0-100 mm) over time between treatment-strategies were compared using linear mixed models with visits clustered within patients. A multivariable model was used to assess the ability of baseline characteristics to predict the chance of high pain-scores during follow-up. Results Pain-scores over time reduced from mean 55.3 (SD 21.7) to 19.5 (SD 25.3) mm after 24 months. On average, pain-scores decreased significantly with β -1.37 mm (95% CI -1.726; -1.022) per month. No significant difference was found between treatment-strategies (interaction term treatment arm*time (months) β (95% CI) arm 1: 0.13 (-0.36; 0.62) and arm 2: 0.37 (-0.12; 0.86) compared to arm 3). Correction for sex and symptom duration yielded similar results. Several baseline characteristics were predictive for pain over time. Higher VAS pain [β 0.44 (95% CI 0.25; 0.65)] and higher active joint count [0.77 (0.19; 1.34)] were predictive of higher pain over time, whereas, low VAS physician [ -0.34 (-0.55; -0.06)], CHQ Physical [ -0.42 (-0.72; -0.11)] and Psychosocial summary Score [ -0.42 (-0.77; -0.06)] were predictive of lower pain. Conclusions Treatment-to-target seems effective in pain-reduction in non-systemic JIA-patients irrespective of initial treatment-strategy. Several baseline-predictors for pain over time were found, which could help to identify patients with a high risk for development of chronic pain. Trial registration Dutch Trial Registry number 1574.